Autotoxicity in Panax notoginseng of root exudatesand their allelochemicals - Xiang, Wei; Chen, Jianhua; Zhang, Fengyuan; Huang, Rongshao; Li, Liangbo (Frontiers in Plant Science, 2022)
The growth of Panax notoginseng is often hindered by replant failure. In this study, we aimed to investigate the role of autotoxicity in the failure of P. notoginseng replantation and assess the role of organic acid in autotoxicity. The autotoxicity was measured using seedling emergence bioassays and continuously cultivated soil water extracts were used to simulate the autotoxicity stress. The results showed that the seedling emergence and survival rate decreased significantly with the increasing planting years, starting from one to three years. The autotoxicity of P. notoginseng was investigated in hydroponics either with or without activated charcoal (AC) addition. In P. notoginseng grown in non-renewed culture solution without AC, the fresh and dry mass of roots was reduced by about half compared with those with AC. A total of 44 different components were identified from all samples based on the GC-MS analysis. Furthermore, the results of multiple statistical analysis showed a qualitatively correlation between these components and the difference cultivated soil with P. notoginseng and the uncultivated soil. Bioassay of the identified allelochemicals revealed that benzoic acid, phthalic acid, salicylic, palmitic acid, and stearic acid significantly affected root growth of P. notoginseng. These substances at 100 μM more significantly decreased the number of lateral roots.